Konservasi Pusaka Budaya Istana Taman Ujung Karangasem - I Wayan Tagel Eddy (Jurnal Kajian Bali (Journal of Bali Studies), 2013)
AbstractTaman Ujung is a heritage of Karangasem kingdom.Construction of the park was created in 1909 until 1925.Taman Ujung Karangasem is a masterpiece of architecturewith the concept of the floating gardens and open spaceswith a background of mountain scenery and beaches.At Mount Agung erupted in 1963 and 1976 earthquakeresulted in physical damage to the construction of TamanUjung. This damage into early problems that arise in themanagement of Taman Ujung Karangasem. At this timethe matter accumulates, that Taman Ujung a heritagearea that is not maintained because it has not had a sitemanagement plan that could be used for investors, thereis no institution that coordinates the commitment andcontribution of multiple stakeholders, and not maximal inthe interpretation and presentation of heritage.For the purpose of Taman Ujung as a tourist destinationneeds wisdom and strategy should be prepared to supportthe conservation and revitalization plan so that appropriatesteps should be taken in the conservation of the TamanUjung Karangasem as one of the cultural heritage inKarangasem regency, Bali.